Minimum variance portfolio in ASEAN-6 stock markets diversification: A Vietnamese perspective - Tri M Hoang (Cogent Business & Management, 2022)
Using daily and monthly MSCI index returns of Association of Southeast Asian Nations (ASEAN) markets for the period 2007 and 2021, this study aims to examine if there are any advantages to diversification in ASEAN markets for Vietnamese investors and if those perks have altered between pre and post 2008 financial crisis (period 1) and pre and during the Covid-19 pandemic (period 2). Correlations are evaluated pre and post crises using both an 86-month correlation window for the whole period and a 12-month rolling correlation window. To assess the benefits of diversification, several portfolios are built employing the Markowitz Portfolio Optimizer using a minimum-variance (MV) reference. Correlations between ASEAN emerging markets have risen between before and after crises. Diversification advantages are available to Vietnamese investors, although benefits have declined during crises, and they seem to be stronger in emerging markets than in Singapore (a developed market). As a result, this paper suggests that Vietnamese investors should look other alternative approaches than the MV portfolio method to minimize investment risks during crises. Vietnamese investors also need to prepare different investment strategies for each period as the perks of ASEAN diversification in periods 1 and 2 are not the same.
Keywords: G11; G15; C14; 650; ASEAN Equity Markets; Asset Correlations; International Diversification; Portfolio Diversification Benefits